Computer scheduling of gasoline deliveries from one depot to a number of delivery points - Suchada Jirakraisri; Oudheusden, Dirk L. van; Shrestha, Ram M.; Bohez, Erik L.J.; The Royal Government of the Netherlands (Bangkok : Asian Institute of Technology, 1992)
The study is concerned with the optimum routing and scheduling of a fleet of gasoline delivery trucks between a central depot and a large number of service stations supplied by the depot. The travel time between any two points in the system is assumed given and a total quantity demand for products and a delivery acceptance period are specified for a number of stations within the distribution system. There are two types of time windows that have to be considered. One is according to the specified delivery acceptance period of stations and the other is due to travel regulations of trucks. They can travel only in specific periods. It is desired to find a way to assign stations to trucks in such a manner that station demands are satisfied within the delivery acceptance period and total time covered by the fleet is a minimum. Additional constraint of travel regulations on trucks may not be violated. A procedure based on a heuristic algorithm is given for obtaining a near optimal solution.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1992
Keywords: Scheduling (Management); Gasoline -- Transportation